DOSIS PUPUK KANDANG DAN TANAMAN SISIPAN CABE (Capsicum annum L.) PADA PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogeal L.) - Djoko Setyo Martono; Wuryantoro Wuryantoro; Nazil Abdi Muqorobin (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
Peanut (Arachis hypogaea L.) in Indonesia is an important agricultural commodity after soybean, which has a strategic role in the national food system as a source of protein and vegetable oil. Chili (Capsicum annum L.) is a horticultural commodity with good prospects. The community widely uses it as a cooking spice, an ingredient in traditional medicine, and a mixture in the food industry. The insertion of chili plants into peanut plantations will increase the effectiveness and efficiency of nutrient utilization from the given manure and have a positive economic impact. This study aimed to determine the effect of doses of goat manure and the insertion of chilies on the growth and yield of peanut plants in the intercropping system of intercropping plants. The study used a randomized block design (RBD) with two factors. The dosage of manure with three levels D1 = 2.5 kg goat manure, D2 = 5.0 kg goat manure, and D3 = 7.5 kg goat manure as the first factor, and the insertion of chili plants at the following levels: S0 = monoculture and S1 = relay cropping with chili as the second factor. The results showed an interaction between the treatments of various doses of goat manure (D) and the addition of plant inserts (S) on plant height aged 56 days after planting, fresh weight, dry weight, and peanut weight. The treatment of various doses of goat manure was not significantly different in all parameters except plant height 42 days after planting. Treatments of chili as relay cropping were not significantly different on all parameters except the weight of 100 peanut seeds. The higher dose of manure causes a decrease in the production of peanuts, which are inserted into the chili plants, but the amount of goat manure can increase the leaf area of the staple peanut plant but has no impact on the total growth/plant dry weight.